(untitled) (Homoeopathy for All, 2026)
There is a moment every homoeopathic physician knows. The patient is sitting before us. The case has been taken with care. The symptoms have been weighed, the modalities examined, the mental and physical generals understood, and the totality has slowly begun to point toward a remedy. After much thought, the prescription is written Then, almost silently, another question rises. Which company’s medicine should I give? Is this Sulphur 30 truly comparable with another Sulphur 30? Is this Natrum muriaticum 200 from one pharmacy the same in quality, preparation, and reliability as the same medicine from another manufacturer? When I place a small bottle in the hands of my patient, am I only relying on my knowledge of materia medica, or am I also silently trusting a chain of pharmaceutical processes that I cannot fully see? This question has lived with me since 1990, when I began my practice. It has followed me through thousands of prescriptions, countless follow-ups, and many moments of clinical uncertainty. It became even sharper when I taught homoeopathic pharmacy to undergraduate students at Bakson Homoeopathic Medical College. I was not only teaching them the technical preparation of medicines. I was preparing them for the realities of practice.